استخالص وتقدير الفعالية البيولوجية لبذور نبات Tribulus terrestris L - (:unkn) unknown (جامعة الوادي - university of eloued, 2024)
The aim of this study is to extract and estimate the biological effectiveness of Tribulus terrestris L seeds. The seeds were ground and extracted with the following solvents: distilled water, ethanol, and a mixture of water and ethanol (3/7). A phytochemical survey revealed the following compounds: phenolics, alkaloids, flavonoids, and terpenes, and they were rich in these compounds . After the extraction process, the extraction yield was calculated, and the extract of a mixture of water and ethanol had the highest value, with a percentage of 18%. After that, the phenols were quantitatively estimated. The results showed that the capacity of the ethanolic extract was the highest value and was estimated at (EqAG mg/g) 410.8. Flavonoids were also quantitatively estimated. The highest value was estimated in the extract of a mixture of water and ethanol at (EqQr mg/g) 209.29, and then the antioxidant activity was estimated in two tests: the DPPH test and the FRAP test, where we found that the ethanolic extract had the largest value for antioxidant activity. Finally, the biological antibacterial activity was studied, where Then four strains of bacteria were tested at different concentrations, and the results showed that the bacteria possessed resistance to some of the studied extracts .
Keywords: Tribulus terrestris L; determination of antioxidant activity; DPPH test; FRA test; biological antibacterial activity